Enhancing Early Childhood Learning Through Parental Risk Mitigation - Ririn Aminah; Terza Travelancyah; Ivonne Hafidlatil Kiromi (Universitas Nurul Jadid, 2024)
This research aims to understand how parents can design and implement risk mitigation strategies in early childhood education by utilizing local wisdom. This research will examine the role of local wisdom in reducing the negative impact of social media and strengthening the formation of children's character and social skills. The qualitative research approach uses interviews and observations of parents actively integrating local cultural values into their children's education. The research results show that parents who understand and master local wisdom in children and integrate it into their parenting can create an effective local wisdom-based learning environment. Additionally, collaboration with the community to expand learning has also proven beneficial. This research provides important implications regarding the need to integrate local wisdom in early childhood education as an effective effort to reduce harmful risks. Therefore, this research contributes to developing local culture-based education policies that can improve children's quality of education and social development.